Evaluation of Compatibility and Bio-efficacy of Certain Agrochemicals Against Leafhopper, Empoasca kerri (Pruthi, 1940) (Hemiptera: Cicadellidae) in Soybean - Anil, Methuku; Hugar, Shiddalingappa V.; Channakeshava, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Lack of knowledge regarding compatibility of agrochemicals can result in emergence of resistance in insects, reduced effectiveness of the chemicals and potential for phytotoxicity. Hence, Studies were conducted to evaluate the compatibility and efficacy of recommended agrochemical in soybean against leafhoppers at Agricultural Research Station, Sankeshwar, Karnataka during 2022-23 with fifteen treatments and three replications. Diafenthiuron 50 WP + Propiconazole 25 EC + 19:19:19, Dinotefuran 20 SG + Propiconazole 25 EC + 19:19:19 and Diafenthiuron 50 WP + Tebuconazole 50 + Trifloxystrobin 25 WG + 19:19:19 recorded 2 ml l-1, 1 ml l-1 and 2 ml l-1 of sedimentation, respectively which was less than the limits of 2 ml 100 ml-1 as specified by Indian Standard Institute, 1973. The pH of all the test solutions were in the range of 6.44 to 8.36 there wasn’t much difference in the pH hence, treatments were found compatible both physically and chemically. Among different treatments tested in field Thiamethoxam 25 WG alone (3.15 leafhoppers/3 leaves) and its combination treatments viz., Thiamethoxam 25 WG + Propiconazole 25 EC + 19:19:19 (3.37 leafhoppers/3 leaves) and Thiamethoxam 25 WG + Tebuconazole 50 + Trifloxystrobin 25 WG + 19:19:19 (3.60 leafhoppers/3 leaves) found effective in managing leafhoppers population.